Konsep Municipal Cultural Planning dalam Ruang Budaya di Kecamatan Klojen, Kota Malang - Setijawan, Arief; Subagyo, Widyanto Hari; Arani, Tiara Difa (Jurnal Pembangunan Wilayah dan Kota, 2021)
There is a cultural potential that can be used as a cultural resource in Klojen District, which is the center of Malang City, so that it is necessary to organize a cultural space based on the concept of Urban Cultural Planning from the variables and theories studied so that it is integrated into each cultural object. The concept of Urban Cultural Planning referred to in this study is a process that is identified and integrates the use of cultural resources for human and community development at the research location. The purpose of this research is to compile the concept of Urban Cultural Planning in the cultural space in Klojen District, Malang City. This research was conducted with the first stage, namely the cluster delineation of the cultural space area of the Urban Cultural Planning concept from the analysis of the identification of cultural resources, analysis of material materials (analysis of cultural mapping), and analysis of the function center. Developing a strategy that is the basis of the City Cultural Planning concept with SWOT analysis and drafting the concept with expert decisions using descriptive analysis of expert judgment. The results of this research are the compilation of the concept of Urban Cultural Planning in the cultural space in Klojen District, Malang City as the utilization of cultural resources for human and community development at the research location. The concept of urban cultural planning compiled in this study is entitled Colonial Historical Tourism, where in the past during the Dutch colonial era, the distribution of residential areas was divided into areas of Europeans, natives, Chinese, and Arabs. The distribution of residential areas is what underlies the cluster elaboration of the drafting of the Urban Cultural Planning concept with each cluster of areas having their respective functions and nuances as well as a concept center located in Malang City Square as a place for cultural performances and a place to gather together with family time